IDENTIFIKASI KESULITAN BELAJAR MATEMATIKA SISWA PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL DI SMP NEGERI 1 PUJUT - Amalia, Rizki Rahmatul; Muzaki, Ahmad; Kurniawan, Ade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify the learning difficulties of junior high school students in the material of Linear Equations and Inequalities in One Variable (LEOV and LIOV) at SMP Negeri 1 Pujut. The research employs a qualitative descriptive approach involving 55 students from classes VII-3 and VII-5. Data were collected through written tests, interviews, and documentation. The results showed that overall concept understanding was at a moderate level with an average achievement of 48.8%. The distribution of student abilities showed 41.82% in the high category, 23.64% in the medium category, and 34.54% in the low category. The lowest achievement was found in the indicator of applying concepts in problem solving (40.0%), while the highest was in restating concepts in one's own words (55.0%). The main difficulties experienced by students include errors in interpreting equality signs, incorrect transposition of terms, and failure to determine the solution set. Factors contributing to these difficulties include procedural-only learning approaches, lack of conceptual understanding, and insufficient variation in practice problems. These findings suggest that teachers should implement contextual and problem-based learning approaches to strengthen students' conceptual understanding.